The Positive and Negative Impacts of TikTok Dancing on Children in the School Environment - Raihanahh, Raihanahh; Amalia, Rizka (Global Education Journal, 2025)
TikTok is a social media platform that allows its users to create and share short videos with a duration of several seconds to several minutes. This makes understanding its impact on children's learning and social emotional development very important. The purpose of this study was to describe the positive and negative effects of TikTok dance content on the social emotional, motor, and character development of early childhood in schools. The research method was carried out using a qualitative descriptive approach. Data collection was carried out through interviews with teachers and parents, documentation of children's involvement in TikTok dance, and participatory observation of dance activities. The results of the study showed that TikTok dance activities had positive and negative impacts on each child in terms of academics, social skills, and character.